Germany : Report on the Observance of Standards and Codes (ROSC). (IMF Staff Country Reports; Country Report, 2011)
This paper presents the report on observance of standards and codes (ROSC) for the financial sector prepared in connection with the financial sector assessment program (FSAP). The FSAP covers the Basel Core Principles for effective banking, the International Association of Insurance Supervisors (IAIS) principles for regulation, the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation, the Committee on Payment and Settlement Systems (CPSS), and IOSCO Recommendations for Central Counterparts. Germany's essential solid institutional frameworks for macroeconomic policies are also overviewed.